2003
DOI: 10.1046/j.1440-1754.2003.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease and alopecia areata in childhood

Abstract: Coeliac disease is a genetic, immunologically mediated small bowel enteropathy that causes malabsorption. The immune inflammatory response to gluten frequently causes damage to many other tissues of the body. We report the association of coeliac disease and alopecia areata in two children, a 13-year-old girl and a 29-month-old girl. Both of our patients had immunoglobulin A (IgA) class endomysial antibodies, IgA and immunoglobulin G (IgG) antigliadin antibodies and subtotal villous atrophy on jejunal biopsy. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 30 publications
1
26
0
2
Order By: Relevance
“…The response of AA in CD patients to GFD is controversial. Some studies have reported a complete regrowth of scalp and other body hair in CD patients with AA [30,37], while others did not find any response [38,39]. …”
Section: Mucocutaneous Manifestations Of CDmentioning
confidence: 99%
“…The response of AA in CD patients to GFD is controversial. Some studies have reported a complete regrowth of scalp and other body hair in CD patients with AA [30,37], while others did not find any response [38,39]. …”
Section: Mucocutaneous Manifestations Of CDmentioning
confidence: 99%
“…Some cases of alopecia areata associated with CD have been reported [132134]. The administration of a GFD to these patients has variable results, and not in all cases, the recovery of hair growth with the diet [133] has been described.…”
Section: Autoimmune Disorders In Celiac Diseasementioning
confidence: 99%
“…CD may be associated with various skin manifestations, such as dermatitis herpetiformis (DH), psoriasis, alopecia areata and vitiligo [39][40][41]. DH is most frequently found in adolescents, young and middle-aged adults.…”
Section: Celiac Disease and Dermatological Diseasesmentioning
confidence: 99%